2019
DOI: 10.1080/20013078.2019.1582237
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls associated with lipophilic fluorophore staining of extracellular vesicles for uptake studies

Abstract: Post-staining of extracellular vesicles (EVs) with lipid-anchored fluorophores (LAFs) such as PKH67 is a widely used strategy for studying EVs but it is associated with several pitfalls. The pitfalls discussed in this commentary are related to LAF labelling of non-EV species due to (1) lipoprotein contamination in EV samples, (2) desorption of the LAF reporters from vesicles into proteins and lipoproteins in blood and serum, and (3) the capability of the amphiphilic LAF compounds to form EV-like particles. Awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 27 publications
5
99
0
Order By: Relevance
“…These compounds are lipid‐like molecules with fluorescent head groups and long aliphatic tails capable of inserting into the vesicle membrane and have become of extensive use for fluorescence‐based studies of EVs [16–19]. The major drawback of lipophilic tracers, however, is that they are not EV specific and indiscriminately stain all lipid‐containing particles and vesicles within the sample [29,30]. Likewise, being lipophilic, they can also redistribute from the EVs to the cellular membranes.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are lipid‐like molecules with fluorescent head groups and long aliphatic tails capable of inserting into the vesicle membrane and have become of extensive use for fluorescence‐based studies of EVs [16–19]. The major drawback of lipophilic tracers, however, is that they are not EV specific and indiscriminately stain all lipid‐containing particles and vesicles within the sample [29,30]. Likewise, being lipophilic, they can also redistribute from the EVs to the cellular membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Though lipid‐anchored fluorophores were reported to label non‐EV serum components which might decrease the combination efficiency with EVs, PKH26 is still a common choice to track EVs to qualitatively investigate the internalization behavior by cells. [ 43 ] In addition, the initial sizes of two vesicles were similar, thus the membrane fusion or intercalation concerns brought by lipophilic dyes could be eliminated. [ 44 ] Besides PKH26 (red) 3,30‐octadecyloxacarbacyanate perchlorate (DiO, cell membrane green fluorescent dye) and DAPI were used for cytomembrane and nucleus staining.…”
Section: Resultsmentioning
confidence: 99%
“…By using in vitro cultures, we were able to use the ideal conditions to generate EVs and optimise experiments. Specifically, by culturing in serum free media, we eliminated contamination from bovine EVs present in FBS (16) and subsequent false positive fluorescence signals from serum lipoproteins (17). Nevertheless, harvesting large EVs from any source presents challenges as cells or cell debris, including intracellular vesicles released due to parent cell membrane rupture from early centrifugation steps, can contaminate the subsequent EV pellets.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have identified that lipid dye aggregates can mimic EVs when using fluorescence lipid markers (17). We used Triton-X 100 treatment (18)…”
Section: Evs Are Highly Heterogeneous and Differentially Express Ev Mmentioning
confidence: 99%